Notes for a pluralistic philosophy of research practices in psychology - Venturelli, A. Nicolás (SCT Proceedings in Interdisciplinary Insights and Innovations, 2024)
Defining ways of assessing progress in psychology is a pressing problem, especially considering the multiple nature of the object of psychological study, which spans behavioral, cognitive, and experiential dimensions, as well as the axiological density of a science ultimately directed at human behavior. The scope of some forms of scientific pluralism (Wendt & Slife 2009, Chang 2012, Mitchell 2012, Mattu & Sullivan 2021), a position that favorably values the coexistence of theoretical models and other epistemic resources, was explored here for psychology. Part of the motivation for this consisted in erecting a strategy to dismiss the still commonplace (Goertzen 2008, Zittoun et al. 2009, Uher 2021) alarm calls under the idea of a crisis lurking in the field. The hypothesis that these are largely tied to underlying unificationist standards was articulated and supported. A pluralist position inspired by the pragmatism of Mitchell (2012) and Chang (2012), in particular, his notion of pluriaxial regimes in science, was delineated. Such a pluralist epistemology at the same time supports a particular stance on research practices and the division of labor in psychology, which places description and classification as core activities. In addition to making possible an optimistic view of progress in psychology, it thus offers another way of relaxing the neat and limiting division between descriptive-classificatory and explanatory objectives, which at the same time makes it possible to encompass descriptive practices of disparate scope and oriented towards multiple ends